The Effect on the Kidney in Patients With Anti-N-methyl D-aspartate Receptor Antibody Encephalitis - Liu, Lizhi; Gu, Meifeng; Liu, Jia; Liu, Qing; Xu, Xiaofeng; Fan, Rong; Peng, Fuhua; Jiang, Ying (Frontiers in Neurology, 2021)
Objectives: The function of N-methyl-D-aspartate receptor (NMDAR) in kidney has been studied. However, the effect on kidney in anti-NAMDAR antibody encephalitis has not been investigated thus far. Methods: Case data were collected from 82 patients with anti-NMDAR antibody encephalitis, and 166 age- and sex-matched healthy controls (HCs). Clinical characteristics, urinalysis (including urine pH and urine specific gravity (SG)), serum creatinine (Scr), and estimated glomerular filtration rate (eGFR) based on Cr levels were evaluated. Results: At initial admission, urine pH levels and urine SG levels in anti-NMDAR antibody encephalitis patients were significantly higher and lower, respectively, than HCs (both p<0.001). There were no significant differences in Scr and eGFR between anti-NMDAR antibody encephalitis patients and HCs. Urine pH levels in patients with anti-NMDAR antibody <1:32 were significantly lower than those in patients with anti-NMDAR antibody ≥1:32 (p=0.029). Urine pH levels were significantly lower (p = 0.004) and urine SG levels were significantly higher (p = 0.027) in follow-up evaluation 3 months after treatment. Conclusions: The changes on urinalysis occur in patients with anti-NMDAR antibody encephalitis. The pathophysiological changes in anti-NMDAR antibody encephalitis were not limited to the CNS.